2016
DOI: 10.1016/j.landusepol.2016.04.040
|View full text |Cite
|
Sign up to set email alerts
|

The driving forces of landscape change in Europe: A systematic review of the evidence

Abstract: Over the past decades, landscapes worldwide have experienced changes (e.g., urbanization, agricultural intensification, expansion of renewable energy uses) at magnitudes that put their sustainability at risk. The understanding of the drivers of these landscape changes remains challenging, partly because landscape research is spread across many domains and disciplines. We here provide a systematic synthesis of 144 studies that identify the proximate and underlying drivers of landscape change across Europe. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
291
0
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 431 publications
(321 citation statements)
references
References 67 publications
10
291
0
20
Order By: Relevance
“…A recent review of studies looking at driving forces of landscape change in Europe (Plieninger et al 2016) similarly determined ''land abandonment and agricultural extensification'' as the most prominent ''proximate driver'' (i.e. following the terminology used by Geist and Lambin 2002).…”
Section: Changes Conversions and Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review of studies looking at driving forces of landscape change in Europe (Plieninger et al 2016) similarly determined ''land abandonment and agricultural extensification'' as the most prominent ''proximate driver'' (i.e. following the terminology used by Geist and Lambin 2002).…”
Section: Changes Conversions and Processesmentioning
confidence: 99%
“…from a descriptive to an analytical approach. The study of the so-called driving forces of landscape change has been promoted and influenced by various methodological contributions (Geist and Lambin 2002;Bürgi et al 2004;Plieninger et al 2016), building on a long tradition in geography and landscape research (Wood and Handley 2001). Already Wirth (1969) asked for a ''general cultural-geographic theory of forces'' and distinguished between economic (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2015, Qviström and Vicenzotti 2016, paralleled by a continuous increase in the use of the term landscape in studies related to, for example, land use, environmental change, agriculture, and land management. The underlying drivers or causes of landscape changes have been investigated by many different approaches, which has resulted in a diversity of terminologies (Meyfroidt 2015, Van Vliet et al 2015a, 2015b, Eiter and Potthoff 2016, Plieninger et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…A review from Plieninger et al (2016) of 144 studies on drivers of landscape change showed that most studies assessed only one case study area at one local spatial scale and they therefore recommend studies that rather do cross-site and cross-country comparisons. They found that some regions are not well covered, e.g.…”
Section: Tools For Landscape Analysismentioning
confidence: 99%